Inhibition of mTORC2/RICTOR Impairs Melanoma Hepatic Metastasis - Schmidt, Katharina M.; Dietrich, Peter; Hackl, Christina; Guenzle, Jessica; Bronsert, Peter; Wagner, Christine; Fichtner-Feigl, Stefan; Schlitt, Hans J.; Geissler, Edward K.; Hellerbrand, Claus; Lang, Sven A. (Neoplasia, 2018)
Mammalian target of rapamycin complex 2 (mTORC2) with its pivotal component rapamycin-insensitive companion of mTOR (RICTOR) is the major regulator of AKT phosphorylation and is increasingly implicated in tumor growth and progression. In cutaneous melanoma, an extremely aggressive and highly metastatic disease, RICTOR overexpression is involved in tumor development and invasiveness. Therefore, we investigated the impact of RICTOR inhibition in melanoma cells in vitro and in vivo with special emphasis on hepatic metastasis. Moreover, our study focused on the interaction of tumor cells and hepatic stellate cells (HSC) which play a crucial role in the hepatic microenvironment. In silico analysis revealed increased RICTOR expression in melanoma cells and tissues and indicated higher expression in advanced melanoma stages and metastases. In vitro, transient RICTOR knock-down via siRNA caused a significant reduction of tumor cell motility. Using a syngeneic murine splenic injection model, a significant decrease in liver metastasis burden was detected in vivo. Moreover, stimulation of melanoma cells with conditioned medium (CM) from activated HSC or hepatocyte growth factor (HGF) led to a significant induction of AKT phosphorylation and tumor cell motility. Blocking of RICTOR expression in cancer cells diminished constitutive and HGF-induced AKT phosphorylation as well as cell motility. Interestingly, RICTOR blockade also led to an abrogation of CM-induced effects on AKT phosphorylation and motility in melanoma cells. In conclusion, these results provide first evidence for a critical role of mTORC2/RICTOR in melanoma liver metastasis via cancer cell/HSC interactions.
EVALuna2:35129